DEVELOPMENT OF FEATHER KERATIN DURING EMBRYOGENESIS OF THE CHICK - Bell, Eugene (The Rockefeller University Press, 1963)
The development of keratin in 9 to 17 day embryonic chick feathers has been studied by x-ray diffraction and cytochemical methods. The x-ray diffraction pattern given by the 9-day feathers contains none of the features seen in the adult pattern. In the 10 to 11 day patterns, besides two diffuse rings centered at 4.7 A and 10 A, two sharp, rather weak rings are seen at 35 A and 4.2 A with slight preferred orientations about the equator and the meridian, respectively. At 12 days, in addition to the foregoing, a sharp intense equatorial reflection at ∼56 A is observed. On treatment with lipid solvents, the 35 A ring is removed; prolonged extraction removes the 4.2 A ring, while blurring the 56 A reflection and enhancing the central low angle scatter. The 14-day pattern shows, besides all the features seen in the earlier patterns, a 23 A meridional reflection and other meridional and near meridional reflections. All the basic features of the adult pattern are seen at this stage and remain essentially intact on lipid extraction. Beyond 14 days, the pattern remains essentially the same, only improving in clarity and detail. The 4.2 A ring seen in the 10 to 15 day pattern is scarcely detectable in the 16-day pattern. Cytochemical evidence indicates that extensive —S—S bond formation occurs between the 13th and 14th days. It is suggested that lipids serve as a framework for the developing keratin structure which acquires permanent stability through hydrogen bonds and disulfide cross-links. The relation between keratin synthesis and tissue architecture as well as cytodifferentiation is discussed.